Appraisal the Importance of Dehydroepiandrosterone, Metabolites, and Genus Aspergillus in Cancer research - AL ANI, RAGHDA (ASJ - Academic Science Journal, 2025)
Steroids are natural compounds found in animals, plants, fungi, and some bacteria. Microbial transformation plays a critical role in the biotransformation of steroids, enabling the production of compounds with high regional and spatial selectivity. Cancer remains one of the most significant scientific challenges, causing millions of deaths each year. Consequently, major research efforts are focused on discovering new therapies, particularly due to the emergence of certain fungi that exhibit anticancer properties, which could lead to innovative treatments. Metabolites, which are intermediate products of biochemical processes in living organisms, are essential for clinical diagnosis. Therefore, accurate detection of their concentrations is crucial. In this work, I will describe an experiment published at the 1st International Karatekin Science and Technology Congress, held from September 1-3, 2022 in Çankırı, Turkey. The aim is to clarify the inputs, outputs, and processes to enhance the understanding of the key concepts discussed here. The experiment focused on incubating dehydroepiandrosterone (DHEA) with Aspergillus glaucus, which primarily resulted in the production of several hydroxylated metabolites. Discussing this experiment as one of the experiments that produces metabolites as a result of the biotransformation of steroids may have a major role in the development of promising treatments for cancer.